(untitled) (e-Journal of Linguistics, 2020)
This study is aimed to analyze the process types of transitivity system in a ritual text of Tawur Sasih Kesanga in Desa Adat Kuta. This research uses primary data contains of transcription of a text that recorded at the ritual and a text that recorded when interview the ritual leader, pemangku. The data was collected by observation method and 1-on-1 interview method. The data is analyzed qualitatively and presented by applying formal and informal methods. The result of this study indicate that there are five (5) types of transitivity processes used in the Ritual Text of Tawur Sasih Kesanga in Desa Adat Kuta, thore are: (1) Material process is used dominantly as many as 73 or 52,9%; (2) The use of relational process is found as many as 40 or 29%; (3) Behavioral process is used as many as 10 or 7,2%; (4) the use of mental process is found as many as 8 or 5,8%; (5) The last one, it’s found that existential process is used as many as 7 or 5,1%.